Analisis Kasus Putusan Sengketa Tanah Garapan Oleh Masyarakat Di Desa Kwala Bingai Kecamatan Stabat : (Tinjauan Putusan Mahkamah Agung Republik Indonesia No: 123/G/2023/PTUN-MDN) - Ade Tamaria Sitanggang; Cindy Nababan; Gelora Sembiring; Oktavia Anjelina Saragih; Rosaria Anastasya Br Sianipar (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
Agricultural land disputes and resolution of certain cases based on the decision of the Supreme Court of the Republic of Indonesia Number: 123/G/2023/PTUN-MDN. Cultivated land disputes are disputes related to the use of land by local communities without the consent of the land owner or government. Case resolution is a legal process that involves legal evidence and appropriate legal interpretation. This decision regulates the settlement of agricultural land between parties managing agricultural land that has not been resolved by the government. The Supreme Court decided that the plaintiff had the right to acquire agricultural land which was considered state land, and other parties had no legal basis to acquire the agricultural land. This decision reflects the legal basis that applies to cultivated land. Land dispute resolution is a complex issue that requires careful and professional handling to avoid conflicts of interest. This study also highlights land ownership and land management issues that require further discussion.